Pelatihan dan Pendampingan Implementasi Aplikasi Kepegawaian Pada SMA PGRI Pagaralam Berbasis Web - Rahmad Hidayat; Andri Andri; Darius Antoni; Hadi Syaputra (Jurnal Nasional Pengabdian Masyarakat, 2021)
The current use of the system at SMA PGRI Pagaralam uses excel and word applications. This is still felt to be ineffective because there is no system that supports these problems. Mentoring training for making personnel applications conducted at SMA PGRI Pagaralam aims to help manage employee data so that it is more effective. Software development is carried out using software engineering rules (software engineering). In software engineering theory there are several kinds of software development process models. This research uses the waterfall model. The water fall model or what is often called the Classic life cycle model shows software development sequentially and systematically. So that the results of the web-based PGRI Pagar Alam high school personnel application include a login system, type of PTK, subjects, leave letters, years of service and subject teachers.